Autorzy:Wojciech Babiański, Lech Chańko, Dorota Ponczek
Wydawnictwo:Nowa Era
Rok wydania:2015
Sprawdź, czy f(-3)=f(1)4.63 gwiazdek na podstawie 8 opinii

`a)` 

`f(-3)=1/2*(-3)^2+(-3)-1=` 

`\ \ \ \ \ \ \ \ \ =1/2*9-3-1=` `9/2-4=4 1/2-4=1/2` 

`f(1)=1/2*1^2+1-1=` `1/2` 

`f(-3)=f(1)` 

`x=(-3+1)/2=(-2)/2=-1 " - oś symetrii paraboli"` 

`x_w=-1` 

`y_w=f(x_w)=f(-1)=1/2*(-1)^2+(-1)-1=` 

`\ \ \ \ =` `1/2*1-1-1=` `1/2-2=-1 1/2` 

`W=(-1,\ -1 1/2)` 

 

 

`b)` 

`f(-3)=-2*(-3)^2-4*(-3)+2=` 

`\ \ \ \ \ \ \ \ \ =-2*9+12+2=` `-18+14=-4` 

`f(1)=-2*1^2-4*1+2=` `-2-4+2=-4` 

`f(-3)=f(1)` 

`x=(-3+1)/2=(-2)/2=-1 " - oś symetrii paraboli"` 

`x_w=-1` 

`y_w=f(x_w)=f(-1)=-2*(-1)^2-4*(-1)+2=` 

`\ \ \ \ =-2*1+4+2=` `4` 

`W=(-1,\ 4)`